Factors associated with low unit cohesion in Australian Defence Force members who deployed to the Middle East (2001–2009) - Kanesarajah, Jeeva (J R Army Med Corps, 2016)
INTRODUCTION: Unit cohesion has been shown to bolster the mental health of military personnel; hence, it is important to identify the characteristics that are associated with low unit cohesion, so that interventions to improve unit cohesion can be targeted and implemented. Little is known about the factors associated with low unit cohesion. This research aims to identify demographic, military service and deployment factors associated with low unit cohesion. METHODS: Data from a self-reported cross-sectional study of 11 411 current or ex-serving Australian military personnel deployed to Iraq or Afghanistan between 2001 and 2009 were used. Multivariable logistic regression was used to investigate the research aims. RESULTS: Being female (adjusted OR (aOR) (95% CI) 1.35 (1.21 to 1.51)), non-commissioned officer (aOR (95% CI) 1.50 (1.39 to 1.62)), lower ranked (aOR (95% CI) 1.74 (1.51 to 2.01)) or having left military service (aOR (95% CI) 1.71 (1.46 to 2.02)) was associated with reporting low unit cohesion. Potentially modifiable factors such as performing logistic roles on deployment (aOR (95% CI) 1.13 (1.01 to 1.27)), dissatisfaction with work experience on deployment such as working with colleagues who did not do what was expected of them (aOR (95% CI) 4.09 (3.61 to 4.64)), and major problems at home while deployed (aOR (95% CI) 1.50 (1.38 to 1.63)) were also associated with reporting low unit cohesion. CONCLUSIONS: This is the first study to identify demographic, military service and deployment factors associated with low unit cohesion. The modifiable nature of unit cohesion means that military leaders could use this information to identify subgroups for targeted resilience interventions that may reduce vulnerabilities to mental health problems and improve the job satisfaction, preparedness and deployment experiences of serving members.